2017
DOI: 10.1097/j.pain.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Interacting influences of gender and chronic pain status on parasympathetically mediated heart rate variability in adolescents and young adults

Abstract: Considerable research links chronic pain to autonomic nervous system (ANS) dysfunction, specifically low heart rate variability (HRV) mediated by reduced parasympathetic activity. However, little is known about factors that influence ANS function in chronic pain. The ANS is the primary pathway for brain–gut communication, making it of particular interest in gastrointestinal disorders, such as irritable bowel syndrome, characterized by functional abdominal pain (FAP). We evaluated the relation of sex, pain seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 55 publications
4
26
0
1
Order By: Relevance
“…It is not clear whether this rigidity is a primary underlying pathophysiologic mechanism or possibley due to chronic stress. The autonomic system rigidity demonstrated in the current study has been previously reported in children with functional abdominal pain when undergoing a psychologic stress task . If it is a primary mechanism, it may be amendable to modalities such as HRV biofeedback.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is not clear whether this rigidity is a primary underlying pathophysiologic mechanism or possibley due to chronic stress. The autonomic system rigidity demonstrated in the current study has been previously reported in children with functional abdominal pain when undergoing a psychologic stress task . If it is a primary mechanism, it may be amendable to modalities such as HRV biofeedback.…”
Section: Discussionsupporting
confidence: 70%
“…This was true whether assessed as the average over the en- task. 26 If it is a primary mechanism, it may be amendable to modalities such as HRV biofeedback. As the rigidity might be due to chronic stress, future studies should address whether it reverses with treatments directed at stress management and importantly, whether any reversal is associated with symptom improvement.…”
Section: Ta B L Ementioning
confidence: 99%
“…18 Research has demonstrated that patients with chronic pain experience self-regulatory depletion, 9,19 which has been theorized to limit the availability of other personal resources (eg, motivation, planning) needed to persist with daily activities or respond adaptively to stress. 18,41 This relationship is exemplified in the current data through a mediational model in which HF-HRV directly influences psychological flexibility, and that, in turn, affects everyday behavior in the context of pain.…”
Section: Discussionmentioning
confidence: 99%
“…While the latter has not been studied directly, research suggests that, among patients with chronic pain, low HRV is associated with poor emotional reactivity, 8 poor adaptability to internal and external demands, 19 and weak behavioral persistence, 18 which are proximate behaviors associated with psychological flexibility. 20 …”
Section: Introductionmentioning
confidence: 99%
“…HRV is a commonly used index in gastroenterology, as it reflects the unbalance between the primary excitatory and inhibitory body systems [104]. ANS is the main communications pathway between brain and intestine, hence it is of particular interest for gastrointestinal disorders, as it is the case of irritable intestine syndrome, which is characterized by a functional abdominal pain [105]. Defining the gravity of the pain according to its duration and intensity, a lower HRV has been related with a higher gravity of abdominal pain in these patients [28,106,107].…”
Section: Gastrointestinal Pain and Hrvmentioning
confidence: 99%